End on a positive note: an exploration of flourishing, identity, and career confidence in professional Australian footballers transitioning out of football - Rist, B.; Quartuccio, C.; Smith, B.; Pearce, A. J. (Science and Medicine in Football, 2025)
This study explored professional male Australian rules football players leaving the Australian Football League (AFL), either from retirement or from deselected from their team. Identified athletes (n = 425) transitioning from the AFL competition from years 2019 to 2021 were invited to participate in an anonymous online survey with 60% completing the survey. Using scaled-response questions, responses were compared between groups across a number of areas including their experience of leaving, athlete identity, the influence of sport in their daily life, psychological flourishing, financial confidence, social relationships, and future career preparations. Results showed deselected players (n = 152), compared to retired players (n = 56), reported shorter career spans, and poorer perception of their club`s handling of the transition process (p < 0.001). Compared to retired players, deselected players reported stronger identity attachment to sport, less confidence in their financial capabilities, and career outside football (all p < 0.05). Conversely retired players, compared to deselected players, showed stronger psychological flourishing. Correlations showed that retired players were more confidence in their finances, reported greater psychological flourishing, and lower attachment to an athletic identity (all p = 0.05). The results of this study suggest that as deselected players expressed poorer perception of club`s handling of the transition process the role of AFL club staff could improve the transition process in in preparation for life outside of professional sport.